Zeitenwende Through the Lens of Olaf Scholz’s Government Strategic Documents - A. P. Sokolov; S. E. Protsenko (Vestnik MGIMO-Universiteta)
This study examines German doctrinal documents issued under the government of Olaf Scholz in the context of the “Zeitenwende” (turning point) proclaimed in 2022. Key documents analyzed include the National Security Strategy, Guidelines for Feminist Foreign Policy, Strategy on China, and Defense Policy Guidelines. Of particular interest are the ongoing transformations in Germany's strategic culture, which are unprecedented in scope and aim to position the Federal Republic as a significant actor in military policy. In response to Russia's military intervention in Ukraine, Berlin has increasingly emphasized the military dimension of its policy, including arms deliveries to Kyiv—an action that marks a departure from the postwar principle of refraining from supplying weapons to conflict zones.The article explores how intra-German debates on military and political issues are reflected in these strategic documents. The participants in these debates can be broadly categorized into three groups: proponents of both the “Zeitenwende” and the government's associated policies; supporters of the “Zeitenwende” who dissent on the methods or tools of implementation; and opponents of the “Zeitenwende” in principle. Using qualitative content analysis, the study identifies contradictions within the documents and inconsistencies in the implementation of Berlin's declared objectives. Many formulations in the documents are characterized by ambiguity, allowing for future revisions or additions. Notably, the Green Party exerts significant influence over the content, promoting a bellicose rhetoric and advocating for an expanded understanding of security issues.The findings suggest that Germany's practical approach remains measured and cautious. However, the incorporation of the “Zeitenwende” principles into strategic documents ensures their longevity, making it unlikely that any future government coalition will disregard these foundational shifts in Germany's military and foreign policy.